A review of stonefly (Insecta; Plecoptera) taxonomic research in Alabama, with new state records and an updated checklist - Grubbs, Scott A. (Illiesia, 2011)
A brief review of the literature on the taxonomy of Alabama Plecoptera is presented. New state records of Leuctra sibleyi Claassen, Zealeuctra claasseni(Frison), Perlesta decipiens (Walsh), and Isoperla decepta Frison areprovided and an updated checklist of 107 Alabama stonefly species is included.
Keywords: Alabama; entomology; Plecoptera; entomologija; vrbnice; new records; checklist; stoneflies